PELAYANAN PUBLIK KESEHATAN PUSKESMAS DALAM MEMBERIKAN KEPUASAN MASYARAKAT DI KABUPATEN SUMENEP - Wibisono, Aryo; Destryana, R. Amilia (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This study aims to determine the index of public satisfaction in public health center services in Sumenep Regency and the relationship between the services to the public satisfaction. The analysis measured the index of public satisfaction and logistic regression methods to determine the effect of the relationship on total satisfaction in the health services of Public Health Center. The results of the study are the alignment between interests and patient satisfaction is still not aligned, there are still differences between interests and satisfaction, the pattern of the result is the relationship between the assurance dimension to the service satisfaction of the public health center, and the results of the index of public satisfaction values show that the results of the community assess the public health center performance is very good by getting an A grade. Keywords: public service, logistic regretion, index of public satisfaction